Elizabeth [videorecording (DVD)] - Kapur, Shekhar, 1945-; Blanchett, Cate, 1969-; Rush, Geoffrey, 1951-; Eccleston, Christopher; Fiennes, Joseph, 1970-; Attenborough, Richard; Gielgud, John, 1904-2000 (Universal, 2003)
Queen Elizabeth I must learn to weigh her counsel carefully and ignore her private yearnings if she is to keep her crown--and her head.